The second docetaxel rechallenge for metastatic castration-resistant prostate cancer: a case report - Ning, Wei; Chang, Pengkang; Zheng, Ji; He, Fan (Frontiers in Oncology, 2023)
Background: Docetaxel combined with prednisone plus androgen deprivation therapy (ADT) is the preferred treatment option for metastatic hormone-sensitive prostate cancer (mHSPC) or metastatic castration-resistant prostate cancer (mCRPC). With the development of next-generation hormonal agents (NHAs) and poly (ADP-ribose) polymerase (PARP) inhibitors, more aggressive first-line or later-line treatment strategies have been added to the treatment of mHSPC and mCRPC. However, docetaxel rechallenge (DR) has special clinical significance in patients with “docetaxel-sensitive” prostate cancer. There are no reports on the efficacy and safety of the second DR in mCRPC patients. Case presentation: We report one patient diagnosed with mCRPC who showed progression-free survival (PFS) and overall survival (OS) benefits and safety and good lower urinary tract function after the second DR. Conclusion: The second DR as a potential alternative later-line treatment strategy should be considered for patients with mCRPC who worry about the high economic burden of multigene molecular testing and PARP inhibitors as well as repeated prostate needle biopsy.